2015
DOI: 10.1371/journal.pone.0144277
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Stromal Tumors: Different Clinicopathologic and Computed Tomography Features in Various Anatomic Sites

Abstract: Gastrointestinal stromal tumors (GISTs) can present with different clinical and immunohistochemical characteristics according to different anatomic sites. The aim of this study was to compare clinicopathologic and computed tomography (CT) features of small bowel stromal tumors located in the duodenum, jejunum, and ileum. In total, 197 patients (109 male, 88 female) with small bowel GISTs were retrospectively reviewed. All tumors had definite anatomic sites in the small bowel tract with surgical confirmation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…In previously published studies, GIST of the small bowel has been reported to show a slight male predominance. 10 , 12 , 13 However, the findings from this study showed there were equal numbers of men and women, which may have been due to the small study sample size. However, the median age of the patients in the present study was 56 years, which was similar to previously reported case series.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In previously published studies, GIST of the small bowel has been reported to show a slight male predominance. 10 , 12 , 13 However, the findings from this study showed there were equal numbers of men and women, which may have been due to the small study sample size. However, the median age of the patients in the present study was 56 years, which was similar to previously reported case series.…”
Section: Discussionmentioning
confidence: 56%
“… 6 , 7 The diagnosis of GIST of the small bowel may be delayed for several reasons, including its relatively low incidence, nonspecific and variable symptoms, the wide spectrum of radiological appearances, intestinal thickening, and the presence of overlapping loops of intestine, which make imaging studies difficult; all of these lead to delayed or misdiagnosis of GIST of the small bowel. 8 – 10 …”
Section: Introductionmentioning
confidence: 99%
“…There are reports in the literature that GIST can have rare manifestations such as intestinal obstruction, perforation or rupture, abscess and intestinal stula [11,12]. However, if it is in ammation caused by GIST, such as abscess formation, it is usually acute and often accompanied by tumor central necrosis and rupture [8]. This patient has been suffering from intermittent abdominal pain and fever for 6 years, and the pathological examination of the capsule is intact.…”
Section: Discussionmentioning
confidence: 90%
“…Although there are reports in the literature that GIST can have rare clinical symptoms such as intestinal obstruction, perforation or rupture, abscess and intestinal stula, etc., it is reported that GIST with the above-mentioned symptoms usually has a tumor diameter greater than 5 cm, even greater than 10 cm [6,7]. And necrosis of small intestine GIST is generally central liquefaction necrosis [8]; Therefore, it is considered that in ammation stimulus and perforation accompanied with formation of abscess cavity after injury, and speculated that the chronic in ammation of the tumor edge is caused by infection caused by trauma. HE staining of postoperative sections showed tumor cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a large series of 906 patients published by Miettinen et al ,28 jejunal and ileal GISTs most commonly presented with GI bleeding or an acute abdomen. In a recent paper by Xing et al ,29 GIST symptoms at presentation were evaluated in 197 patients on the basis of their location in the small bowel. Cardinal symptoms for patients with ileal GISTs included epigastric discomfort (38.3%), abdominal mass (34%), incidental finding (27.7%) and GI bleeding (12.8%).…”
Section: Discussionmentioning
confidence: 99%